Implementation of the Principle of Novelty in the Registration of Traditional Batik Motifs as Industrial Designs in Indonesia - Ruhiat, Dea Rahmawaty; Rafianti, Laina; Ramli, Tasya Safiranita (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2024)
One of intellectual property that has legal protection in Indonesia is industrial design. In Indonesia, industrial design is closely related to the handicraft industry. In Indonesia there is already a registration of industrial designs that use handicraft designs such as traditional batik motif designs which are protected by copyright as an expression of traditional culture. This phenomenon is an overlapping and intersecting issue between the fields of copyright and industrial design. For this reason, legal studies are urgently needed to determine whether a traditional cultural expression can have industrial design novelty or not. This article uses a normative juridical approach, in the form of an analysis of legal principles of Indonesia’s law which is related to research problems. Based on the research results, traditional batik motifs fulfill the elements of an industrial design that can be registered and protected by the industrial design legal framework in Indonesia. The principle of novelty of industrial design can be implemented to filter the novelty of industrial design in selecting registration of traditional batik motifs as industrial designs. The legal protection of traditional batik motifs based on the Industrial Design Law has not been regulated comprehensively and clearly, the legal protection is only regulated as a disclosure of pre-existing industrial designs. A theoretical approach is needed in applying the articles regarding provisions for checking the novelty and registration of industrial designs related to communal intellectual property using the legal principles and theories that underlie the formation of the Industrial Design Law in Indonesia.